Heidegger and the dialogue on language - Heleno, José Manuel (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2021)
Our aim is to think about the dialogue between a Japanese and a inquirer, entitled Aus einem Gespräch von der Sprache. Zwischen einem Japaner und einem Fragendem (1953-54). We try to argue that, although there is no philosophy of language in Martin Heidegger there is a powerful language design that marks the relationship with the being. Language becomes a saying that is an appropriation of what is given, that is, of what appears and becomes present. It is this relationship with the appearing that shows the power and mystery of language.